2016
DOI: 10.1037/cdp0000039
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the African American Women’s Shifting Scale (AAWSS).

Abstract: A structural model was developed based on the Multicultural Assessment-Intervention Process (MAIP) framework that allowed for the exploration of the shifting construct. Implications for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 95 publications
1
59
0
Order By: Relevance
“…In particular, shifting included altering their behavior, mannerisms, or appearance to fit in with White Americans, as well as altering their speech or topic of conversations. A second aspect of shifting also included sensitivity to the perceptions of other African Americans (Johnson et al, 2016). African American women may submerge their abilities, accomplishments, and strengths to support African American men or engage in certain behaviors to avoid accusations from community and family members that they “sold out” (Johnson et al, 2016; Jones & Shorter-Gooden, 2003).…”
Section: Shiftingmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, shifting included altering their behavior, mannerisms, or appearance to fit in with White Americans, as well as altering their speech or topic of conversations. A second aspect of shifting also included sensitivity to the perceptions of other African Americans (Johnson et al, 2016). African American women may submerge their abilities, accomplishments, and strengths to support African American men or engage in certain behaviors to avoid accusations from community and family members that they “sold out” (Johnson et al, 2016; Jones & Shorter-Gooden, 2003).…”
Section: Shiftingmentioning
confidence: 99%
“…For example, Jones and Shorter-Gooden (2003) found that shifting was associated with emotional eating, compulsive shopping, and substance use, as well as anxiety and depressive symptoms. Within organizational contexts, Allison (2010) suggested that shifting was indicative of self-reflection and intellectual work among African American women but required “extra time and energy to navigate.” While negative aspects of shifting have been documented, facets of shifting as a positive and adaptive coping mechanism among African American women have also been noted (Johnson et al, 2016).…”
Section: Shiftingmentioning
confidence: 99%
See 3 more Smart Citations